Aktualisasi Fungsi Lembaga Wali Nanggroe dalam Pelaksanaan Otonomi Khusus Aceh - Muhammad Iqbal; Muhammad; Evarina (Jurisprudensi: Jurnal Ilmu Hukum, 2025)
Aceh is a special autonomous region within the Unitary State of the Republic of Indonesia, as recognized in Article 18B of the 1945 Constitution. The prolonged conflict between the Central Government and the Free Aceh Movement (GAM) was resolved through the Memorandum of Understanding in Helsinki, which laid the foundation for the establishment of the Wali Nanggroe Institution (LWN). The existence of the LWN is regulated under Law Number 11 of 2006 on the Governance of Aceh, as well as Aceh Qanun Number 8 of 2012 and Qanun Number 9 of 2013. The LWN is positioned as an independent customary leadership institution functioning as a unifying body for the Acehnese people under the leadership of the Wali Nanggroe. This study examines whether the existence of the LWN aligns with the concept of Aceh’s special autonomy, evaluates its effectiveness, analyzes its participation in governance, and formulates an ideal framework for its future role. The research employs a normative juridical method with a prescriptive analytical specification, complemented by an empirical juridical approach through literature review and field interviews. The findings indicate that the LWN has not functioned effectively. Its large institutional structure is disproportionate to its duties and functions, resulting in significant budgetary burdens. The perceived political alignment of the Wali Nanggroe has reduced public trust and weakened its neutral role as a unifying figure, particularly amid political dynamics between the Aceh Government and the Aceh Regional People’s Representative Council (DPRA). In addition, the lack of harmonious relations between the LWN and the Katibul Wali has hindered institutional performance. The study recommends revising the relevant qanun by simplifying the institutional structure, clarifying internal relations, and strengthening the independence and moral authority of the Wali Nanggroe within the framework of Aceh’s special autonomy.